Patterns of Childhood Adversities and Their Associations With Adult Victimization Among Incarcerated Men and Women in Spanish Prisons - Aizpurua, Eva (International journal of offender therapy and comparative criminology, 2023)
Adverse childhood experiences (ACEs) are prevalent and have long lasting effects. There is evidence of gender differences in exposure to different types of ACEs, with women experiencing higher levels of sexual abuse and cumulative adversity than men. Despite this, most research examining patterns of adversities have used joint samples, assuming that men and women have comparable profiles. The current study examines if distinct profiles of childhood adversities exist for men and women and analyzes their associations with multiple forms of interpersonal victimization during adulthood. Participants were 2,709 residents (91.6% men and 8.4% women) from eight prisons in Spain, who completed a self-administered survey. Latent Class Analysis revealed different patterns of childhood adversities for men and women. For both groups, higher adversity was associated with interpersonal harm during adulthood.